Milestones of data visualisation on a 4-quadrant diagram - Alexandrino da Silva, A. (ESS Data Visualisation Workshop, 2019)
https://ec.europa.eu/eurostat/cros/system/files/2_ana_alexandrino_silva_0.pdf The evolution that has taken place since the first line, bar or pie charts were invented by William Playfair is remarkable, particularly after the computer advent. The rise of statistical graphics can’t be dissociated from the historical period they’re in. This presentation aims to contribute to the study of theoretical and historical approach of data visualization. It proposes a 4 quadrant model of analysis based on two perpendicular axes that translate the lesser or greater complexity of the graphical design options and the lesser or greater complexity of the concepts represented.